Gut microbiome profiling in systemic sclerosis: a metagenomic approach - Tan, Tze Chin; Chandrasekaran, Lakshmi; Leung, Ying Ying; Purbojati, Rikky; Pettersson, Sven *; Low, Andrea Hsiu Ling (Clinical and Experimental Rheumatology, 2023)
Objectives: The early gastrointestinal (GI) manifestation of systemic sclerosis (SSc) suggests a possible GI microbiota engagement in the pathophysiology and/or progression of SSc. Previous studies have revealed dysbiosis among Caucasian SSc patients. This study extends these findings to Asian SSc patients.